2018
DOI: 10.1103/physrevb.98.165149
|View full text |Cite
|
Sign up to set email alerts
|

Charge and dielectric response to terahertz pulses in the charge-ordered phase of α(BEDTTTF)2I3

Abstract: We investigated the dielectric properties of the charge-ordered phase of α-(BEDT-TTF) 2 I 3 using exact numerical calculations of an extended Hubbard model. The electronic contribution to the electric polarization (electronic polarization)P of the charge-ordered ground state is obtained by directly calculating the current when transfer integrals were changed adiabatically from symmetric integrals to integrals for the charge-ordered phase without inversion symmetry. The angle of P from the positive b−axis is 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…As shown in our previous paper, i n (t) is strongly affected by this finite-size effect when A(t) = 0. 54,55 We therefore consider the dynamics induced by the double half-cycle pulses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in our previous paper, i n (t) is strongly affected by this finite-size effect when A(t) = 0. 54,55 We therefore consider the dynamics induced by the double half-cycle pulses.…”
Section: Resultsmentioning
confidence: 99%
“…Terahertz (THz) pulses are powerful tools for investigating the ultrafast dielectric response of electronic ferroelectrics. [52][53][54][55] The THz-pump optical-probe and secondharmonicgeneration-probe measurements in TTF-CA have revealed the instantaneous re- sponse of charge and the electronic contribution to the electric polarization (electronic polarization). 52 It has been theoretically shown that the instantaneous response originates from the adiabatic nature of the THz-pulse excited state.…”
Section: Introductionmentioning
confidence: 99%